Effect of Electrode Type and Current Strength on the Mass of Substance Reduced at the Cathode in the Electrolysis Process - Fahmi, Jam'an; Ramadhan, Dwi Sapri; Wardana, Dian; Safitri, Wulan Dwi; Zubir, Moondra; Siregar, Nurdin; Manullang, Riska Greselia; Sagala, Novitri Yolanda; Br Sipahutar, Desy Meriani (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
This study investigates the effect of electrode type and current strength on the mass of hydrogen gas produced at the cathode during the electrolysis of sodium chloride solution. A simulation based on Faraday’s law was conducted using three electrode materials—carbon, copper, and zinc—under controlled current settings of 0.10 A, 0.20 A, and 0.30 A for a fixed electrolysis duration of 30 minutes. Current efficiency values were assigned to each electrode to model realistic performance differences, with copper exhibiting the highest efficiency, followed by zinc and carbon. The results show that increasing the current leads to a linear rise in the mass of hydrogen produced for all electrode types, confirming the proportional relationship between electric charge and cathodic reduction predicted by Faraday’s law. Additionally, copper electrodes produced the highest hydrogen yield at all current levels, while carbon generated the lowest, indicating that electrode characteristics influence electrochemical efficiency. Overall, the findings demonstrate that current strength is the dominant factor determining the mass of reduced species at the cathode, whereas electrode material provides a secondary yet significant contribution to electrolysis effectiveness.